Alcohol problems and socio-economic status : a regional study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology at Massey University - Pitcher, Douglas (Massey University, 1981)
The problem was to explore the apparent relations between occupational status and drinking behaviour and to resolve, if possible, the confusions about which status positions were most likely to consume alcohol and experience problems. The thesis investigates the hypothesis that people occupying high status positions are more vulnerable to high levels of alcohol consumption and alcohol related problems. It was presumed that ranking occupations in terms of the Elley-Irving SES scale, and educational attainment would permit the test of this assumed relationship. The study focused on a sample of 869 males selected from a larger survey of health related issues in the five counties which comprise the Wanganui Hospital Board's area. All males over 15 years of age, employed in a full time occupation who were, or ever had been regular drinkers were interviewed about their levels of consumption, and any alcohol related problems they may have experienced. The general trend of the findings suggested an association between alcohol misuse and low SES. A higher percentage of low status drinkers worried about their drinking; regarded themselves as heavy drinkers; were regarded by others as heavy drinkers; and indicated heavy patterns of consumption (400 + grams of alcohol per week). No relationship between SES and regular drinking was found, although a positive association between regular drinking and educational attainment was suggested. The lack of statistical significance restricts the extent to which we can draw any clear inferences as to the nature of the relationships involved. In conclusion it could be stated that although the findings are not significant they suggest occupational vulnerability is more characteristic of low status occupations. Certain methodological inadequacies make it impossible to draw any firm conclusions concerning alternate hypotheses, for example that low SES positions are more vulnerable. Overreporting by the low SES group, and underreporting by those of high status may have biased the findings. An alternative theory is proposed to the effect that both ends of the status occupational hierarchy are characterised by high vulnerability.
Keywords: Alcoholism; New Zealand Social aspects; Alcohol